Agrobiodiversity in home gardens of family coffee farms in the Zona da Mata region of Minas Gerais State, Brazil (Acta Scientiarum. Agronomy, 2026)
Agrobiodiversity can promote food and nutritional security. Agrobiodiverse agricultural systems are frequently found on small family coffee farms with distinct economic, social, and environmental characteristics in Central and South America. Brazil is the world’s largest coffee producer, with the state of Minas Gerais, especially the Zona da Mata mesoregion, being the country’s leading producer, recognized for its small mountainous family coffee farms. The presence and composition of home gardens in Brazilian family coffee farms still lack objective and measurable assessments of species agrobiodiversity. Given the limited knowledge about agrobiodiversity at these properties, this study aimed to: (i) evaluate plant communities and agrobiodiversity in the home gardens of family coffee farms in Zona da Mata of Minas Gerais State, Brazil; and (ii) document the use of plant species in these home garden communities. Evaluations were conducted in the home gardens of five family coffee farms located in the Zona da Mata region of Minas Gerais State, Brazil, with identification, quantification, and determination of Simpson, Shannon–Wiener, Pielou’s equitability, Morisita, alpha diversity, species–individual curve, and species use indices across 0.1-ha plots per farm. Significant variations in the number of individuals were recorded with the presence of fruit-bearing and vegetable species in the evaluated home gardens. There were notable differences in species compositions and agrobiodiversity indices of the home gardens of family coffee farms. Considerable plant diversity and species richness were observed in all home gardens, primarily associated with food, commercial, medicinal, and ornamental uses, contributing to the social function of the land and the preservation of plant diversity.